Physiology of Chatham Island forget-me-not (Myosotidium hortensia) seed : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Seed Science and Technology at Massey University - McGill, Craig Robert (Massey University, 2003)
Chatham Island forget-me-not (Myosotidium hortensia (Decne) Baillon) is endemic to the Chatham Islands where it is mainly confined to the outer islands. There is speculation that seed of M. hortensia is recalcitrant and reports that germination can be slow and erratic. Moreover there is little information on the seed biology of M. hortensia available. In this study the seed structure and composition of the seed storage reserves of M. hortensia were determined. The seed is a dicotyledon. The embryo is predominantly cotyledonary tissue with a only small embryo axis present. There appears to be a single cell thick layer of endosperm tissue between the embryo and seed coat. Food reserves are stored as both protein and oil with no starch reserves apparent. The seed contains 24% oil and therefore can be considered an oilseed. These oil reserves include the commercially important γ-linolenic (cis, cis, cis-6, 9, 12-octadecatrienoic) acid (9% of the fatty acid content). Seed of M. hortensia was evaluated for recalcitrant behaviour by determining if desiccation to low seed moisture content caused a loss of viability. Seed was harvested at two moisture contents, 47.4% (green seed) and 35.5% (black seed), and air dried to a final moisture content of 7.5%. Seed viability and germination performance were monitored at harvest and as moisture content declined. At 7.5% seed moisture content viability was 89% and germination 92% for seed harvested at 47% seed moisture content, and 82% and 78%, respectively, for seed harvested at 36% seed moisture content. Within each colour classification, after desiccation there was no significant difference in germination compared to that at harvest, indicating that M. hortensia seed can be desiccated to a low seed moisture content without loss of germination and is therefore not recalcitrant. Seed stored at 5°C and 7.5% seed moisture content showed no decline in viability after 21 months, but, seed stored at the same temperature and 9.5% seed moisture content showed a significant loss of viability after 9 months storage. The loss of viability at this higher (9.5%) seed moisture content is characteristic of oilseeds, but it is not clear whether the high oil content of the seed alone can account for the loss of viability after nine months storage at a temperature of 5°C. This study confirmed earlier reports that germination of M. hortensia seed is slow and erratic. At maturity seed of M. hortensia is dormant. Seed dormancy is a function of the seed coat rather than the embryo. The dormancy is likely to be a result of either physical constraint of embryo growth or restriction of gas exchange by the seed coat, or a combination of both. Removal or weakening of the seed coat allowed germination to proceed. However, some of the treatments used to weaken the seed coat resulted in an increase in abnormal seedling development. An effective and non-damaging technique for alleviating dormancy was to prick the seed coat with a 0.6-0.8mm diameter dissecting needle in the middle of the cotyledons.
Keywords: Myosotidium hortensia Seeds